Effect of Financial Stress and Behavior on Personal Financial Well-being: Mediating Role of Financial Satisfaction - Mahato, Surendra; Darji , Puja (Molung Educational Frontier, 2026)
Understanding the drivers of personal financial well-being (PFWB) is crucial in the current financial scenario. This study examines the impact of financial stress and behavior on PFWB, utilizing financial satisfaction as a mediator. Survey data from Kathmandu, Nepal, is used to quantitatively study behavioral finance and well-being theories. The hypothesized correlations were tested using PLS-SEM. Financial stress negatively impacts financial happiness and PFWB, but positive financial behavior greatly improves them. Financial satisfaction also partially mediated the effects of financial stress and behavior on PFWB. The study highlights the importance of adopting good financial behaviors and achieving financial happiness to alleviate financial stress and enhance financial well-being. These findings can help policymakers, financial educators, and practitioners develop initiatives that promote financial resilience and long-term well-being.